Erasmus mobilnost na Fakulteti za socialno delo - Petrović Jesenovec, Borut (Socialno delo, 2015)
Although the Faculty of Social Work is the smallest faculty of the University of Ljubljana, it ranks, if we consider mobility numbers, higher then many other, much bigger faculties. The number of in-coming students, for example, has been increasing for at least six years. The report tries to elaborate on some of the reasons why the Faculty of Social Work is doing so well, despite unfavourable conditions.
Keywords: exchange; visoko šolstvo; internationalisation; mednarodne izmenjave; strategy; Erasmus; internacionalizacija; Fakulteta za socialno delo